Enantioselectivity in biotransformation and bioaccumulation processes of typical chiral contaminants. (December 2018) - Xu, Chenye; Lin, Xinmeng; Yin, Shanshan; Zhao, Lu; Liu, Yingxue; Liu, Kai; Li, Fang; Yang, Fangxing; Liu, Weiping
Abstract: Chirality is a critical topic in the medicinal and agrochemical fields. One quarter of all agrochemicals was chiral in 1996, and this proportion has increased remarkably with the introduction of new compounds over time. Despite scientists have made great efforts to probe the enantiomeric selectivity of chiral chemicals in the environment since early 1990s, the different behaviours of individual enantiomers in biologically mediated processes are still unclear. In the present review, we highlight state-of-the-knowledge on the stereoselective biotransformation and accumulation of chiral contaminants in organisms ranging from invertebrates to humans. Chiral insecticides, fungicides, and herbicides, polychlorinated biphenyls (PCBs), pharmaceuticals, flame retardants hexabromocyclododecane (HBCD), and perfluorooctane sulfonate (PFOS) are all included in the target compounds. Key findings included: a) Changes in the enantiomeric fractions in vitro and in vivo models revealed that enantioselectivity commonly occurs in biotransformation and bioaccumulation. b) Emerging contaminants have become more important in the field of enantioselectivity together with their metabolites in biological transformation process. c) Chiral signatures have also been regarded as powerful tools for tracking pollution sources when the contribution of precursor is unknown. Future studies are needed in order to understand not only preliminary enrichment results but also detailed molecular mechanisms in diverse models to comprehensively understand the behaviours of chiral compounds. Graphical abstract: Image Highlights: Scientists have made great efforts to probe the enantioselectivity of chiral pesticides in vitro and in vivo. Chiral PCBs can undergo enantioselective metabolization to hydroxylated (OH)-PCBs by cytochrome P450 enzyme. Stereoselecticity of chiral pharmaceuticals was caused by selective sorption, biodegradation and enantiomeric inversion. Enantioselective uptake and metabolism of chiral α-HBCD were mostly reported in fish, rat, birds and humans. EF s of 1 m-PFOS could be used to assess the pollution sources when contribution of PreFOS is unknown. Abstract : This paper provided a critical review of the enantioselective biotransformation and bioaccumulation of chiral contaminants from in vitro and in vivo studies.